A preoperative scoring system to predict the probability of laparoendoscopic single-site extracorporeal cystectomy in patients with benign ovarian cysts - Tan, Wenwei; Deng, Yuan; Deng, Li; Tang, Shuai; Yao, Yuanyang; Wei, Huanyu; Zhong, Kuiyan; Wang, Yanzhou (Frontiers in Surgery, 2022)
Objective To develop a preoperative scoring system (PSS) to predict whether laparoendoscopic single-site extracorporeal (LESS-E) cystectomy can be performed in patients with benign ovarian cysts. Method We reviewed data on patients who underwent LESS cystectomy between August 2016 and October 2019 at the first Affiliated Hospital, Army Medical University. The independent predictors of LESS-E cystectomy in patients with benign ovarian cysts were identified using multivariate logistic regression analyses. A nomogram for predicting LESS-E cystectomy in patients with benign ovarian cysts was developed, and to simplify the score, we establish a preoperative scoring system to guide the choice of surgical approach in patients with highly probable benign ovarian cysts. Results Our analysis showed that age, BMI, height and the diameter of ovarian cysts were independent predictors of LESS-E cystectomy. A nomogram was developed based on these four factors, which had a concordance index of 0.838 and R2=0.415. To simplify the score, the predicted indicators in the regression model were scored by dividing the beta coefficient by the absolute value of the minimum beta coefficient, and the sum of each predictor score established a PSS. In the total set, the selected cutoff value according to the maximum point of the Youden index was 8, and a preoperative score ≥8 identified patients undergoing LESS-E cystectomy with a positive predictive value of 67.4% and a negative predictive value of 88.6%. Conclusion A PSS to predict the chances of LESS-E cystectomy was established. This system could be helpful for selecting the appropriate surgical strategy for patients with benign ovarian cysts.